Dynamics of abdominal symptoms during the start of a new therapy with elexacaftor/tezacaftor/ivacaftor using the novel CFAbd-day2day questionnaire - Jochen G. Mainz; Jochen G. Mainz; Anton Barucha; Anton Barucha; Pu Huang; Pu Huang; Lilith Bechinger; Lilith Bechinger; Franziska Duckstein; Franziska Duckstein; Louise Polte; Louise Polte; et al. (Frontiers Media S.A., 2023)
Background: Elexacaftor-tezacaftor-ivacaftor (ETI) is a novel, highly effective CFTR modulator combination proven to enhance lung function and body weight in people with cystic fibrosis (pwCF) carrying a F508del mutation. Recently, we revealed significant reductions in abdominal symptoms (AS) in German, British, and Irish pwCF after 24-26 weeks of ETI using the CFAbd-Score, the first patient-reported outcome measure (PROM) specifically developed and validated for pwCF following FDA guidelines. Notably, many pwCF reported marked changes in their AS during the first days of the new treatment. To capture these immediate effects, we developed the CFAbd-day2day, a CF-specific GI-diary, following FDA and COSMIN guidelines.Aim: To prospectively capture the immediate dynamics of AS using the CFAbd-day2day 14 days before and 14-28 days after ETI initiation. In addition, we aim to provide validation steps of the novel PROM concerning sensitivity to changes.Methods: To develop the CFAbd-day2day, focus groups (community voice = pwCF and their proxies and CF specialists from different fields) were repeatedly consulted. Before and during the new ETI therapy, pwCF prospectively scored AS on a daily basis with the CFAbd-day2day.Results: Altogether, 45 pwCF attended in five CF centers prospectively completed the CFAbd-day2day before (mean ± sd:14 ± 7 days) and after (mean ± sd: 28 ± 23 days) ETI initiation. On the one hand, cumulative scores significantly decreased during the 3-4-week time frame after ETI initiation, compared to 2 weeks prior to therapy. On the other hand, many patients who revealed a relatively stable level of AS before ETI reported changes during the first days of treatment with the highly effective CFTR modulators. Factors like pain and flatulence increased in up to 21% of patients during the first 14 days of therapy, but they improved during days 15-27.Conclusion: The CFAbd-day2day, specifically developed and in the process of validation to prospectively capture GI symptoms in pwCF, provides new substantial insights into the dynamics of AS in pwCF receiving a new treatment with ETI. This novel tool is also helpful in prospectively monitoring patients with specific GI problems. International implementation and further validation steps of the diary are ongoing.